Impact of WHO Hand Hygiene Improvement Program Implementation: A Quasi-Experimental Trial. (23rd November 2016) - Farhoudi, Farinaz; Sanaei Dashti, Anahita; Hoshangi Davani, Minoo; Ghalebi, Nadiyeh; Sajadi, Golnar; Taghizadeh, Raziyeh
Abstract : Objectives . As affirmed by the World Health Organization (WHO), hand hygiene is the most powerful preventive measure against healthcare-associated infections (HCAIs) and, thus, it has become one of the five key elements of patient safety program. The aim is to assess the effect of implementation of the WHO's Multimodal Hand Hygiene Improvement Strategy among healthcare workers of a tertiary teaching hospital in a developing country. Methods . Hand hygiene compliance was assessed among healthcare workers, according to five defined moments for hand hygiene of the WHO, before and after implementation of the WHO's Multimodal Hand Hygiene Improvement Strategy in fourteen wards of a tertiary teaching hospital in Shiraz, Iran. We used direct observation method and documented the results in WHO hand hygiene observation forms. Results . There was a significant change in compliance before and after implementation of WHO's Multimodal HH Improvement Strategy (29.8% and 70.98%, resp.). Conclusions . Implementing WHO hand hygiene program can significantly improve hand hygiene compliance among nurses.